Human leukocyte antigen mismatch on lung transplantation outcomes. (28th February 2022) - Firoz, Ahad; Kashem, Mohammed; Zhao, Huaqing; Geier, Steven; Toyoda, Yoshiya
Abstract: OBJECTIVES: Human leucocyte antigen (HLA) mismatch is a known risk factor for renal transplantation; however, there are conflicting and limited data on its ramifications within lung transplantation (LTx). Therefore, our study evaluated the effects of total HLA, HLA-A, -B and -DR mismatches on LTx outcomes. METHODS: We retrospectively examined the United Network for Organ Sharing database for adult patients who had undergone LTx for the first time between January 2005 and July 2021. Total HLA mismatch (0–3, 4, 5 and 6) and HLA locus mismatch (0–1 and 2) were analysed, with the end points of interest being mortality and bronchiolitis obliterans syndrome (BOS) development. RESULTS: Kaplan–Meier curve analysis found a significant difference in both overall survival ( n = 27 651; 11 830 events) and BOS development ( n = 25 444; 8901 events) for the total number of HLA ( P < 0.001, P < 0.001), HLA-A ( P < 0.001, P = 0.006) and HLA-DR ( P < 0.001, P < 0.001) mismatches. With reference to 0–3 total HLA mismatches, multivariable Cox regression model found that 6 mismatches had an increased risk of mortality ( P = 0.002) while 4 ( P = 0.010), 5 ( P = 0.007) and 6 ( P < 0.001) mismatches had an increased risk of BOS. HLA-B mismatch was not associated with an increased mortality ( P = 0.975) or BOS risk ( P = 0.512). CONCLUSIONS: This study demonstrates a significant relationship between increased HLA mismatches and BOS development, with decreased overall survival only apparent with 6 mismatches. HLA-A and -DR mismatches were associated with an increased risk of mortality and BOS development compared to groups with at least 1 locus match. Abstract : Lung transplantation (LTx) offers an extended lifespan and improved quality of life for many patients with advanced refractory lung disease.